(untitled) (Indian Journal of Case Reports, 2020)
Pigmentation of the tongue can occur due to various physiological or pathological events with no significant difference between males and females and age groups. Change in the color of the tongue can be due to localized lesions or systemic disorders. Oral pigmentation has been associated with a variety of endogenous and exogenous etiologic factors. This case report was about a 40-year-old male patient who presented with fever and pigmentation of tongue and lips. In view of his pigmentation and sudden deterioration in condition, a diagnosis of Addison’s crisis was considered. A computerized tomography scan of his abdomen showed a hypodense non-enhancing lesion in the right adrenal gland, suggestive of tuberculosis. He was started on steroids and antitubercular regimen of rifampicin, isoniazid, ethambutol, and pyrazinamide. After 1 month of treatment, the pigmentation of the tongue and the lips started decreasing.